Binding memory of liquid molecules - Shiyi Qin; Zhi Yang; Huimin Liu; Xiaoli Wang; Bing Miao; Shangguo Hou; Kai Huang (Nature Communications)
Abstract Understanding the binding dynamics of liquid molecules is of fundamental importance in physical and life sciences. However, nanoscale fast dynamics pose great challenges for experimental characterization. Conventionally, the binding dynamics have been assumed to be memoryless. Here, we integrate large scale computer simulation, scaling theory, and real-time single particle tracking microscopy with high spatiotemporal precision to unveil a universal memory effect in the binding dynamics of liquid molecules. This binding memory can be quantified by a binding time autocorrelation function, whose power-law decay depends on binding affinity, the topological and materials properties of the surrounding environment and the heterogeneity of the binding landscape. Context-dependent biomolecular binding memory is likely exploited by biological systems to regulate biochemical reactions and biophysical processes. Deciphering this binding memory offers a novel strategy to probe complex biological systems and advanced soft materials.